Changes in under-shoe traction and fluid drainage for progressively worn shoe tread. (October 2019) - Hemler, Sarah L.; Charbonneau, Danielle N.; Iraqi, Arian; Redfern, Mark S.; Haight, Joel M.; Moyer, Brian E.; Beschorner, Kurt E.
Abstract: Shoe wear is known to increase slipping risk, but few studies have systematically studied this relationship. This study investigated the impact of progressive shoe wear on the available coefficient of friction (ACOF) and under-shoe fluid dynamics. Five different slip-resistant shoes were progressively worn using an accelerated, abrasive, wear protocol. The ACOF and fluid forces (the load supported by the fluid) were measured as shoes were slipped across a surface contaminated with a diluted glycerol solution. As the shoes became worn, an initial increase in ACOF was followed by a steady decrease. Low fluid forces were observed prior to wear followed by increased fluid forces as the worn region became larger. Results suggest that traction performance decreases particularly when the heel region without tread exceeds a size of 800 mm 2 . This study supports the concept of developing shoe replacement guidelines based upon the size of the worn region to reduce occupational slips. Highlights: Slip-resistant shoes were worn using a novel, accelerated wear protocol. Available coefficient of friction (ACOF) and fluid pressures were measured. Prolonged wear decreased ACOF and increased under-shoe fluid forces. The size of the fully worn outsole region may be a good shoe replacement indicator.